Lunar Science Habitat and Humans - Chemin, Yann-Henri (IntechOpen, 2022)
There are still many open scientific questions about the moon, including whether humans will one day be able to live there. This book looks at the history of the moon's orbit and the prospects of in situ lunar science, the radiation impact on the lunar surface, the resistance of settlement materials on the moon under the conditions of protecting humans on-site, and the preparation of humans for space missions.